2014
DOI: 10.1177/0011000014524600
|View full text |Cite
|
Sign up to set email alerts
|

Critical Secret Disclosure in Psychotherapy With Korean Clients

Abstract: Korean clients who had completed counseling in Korea and viewed the therapy as successful were interviewed about critical secret disclosure during their therapy. In-depth interviews along with grounded theoryinformed analyses in a methodological hermeneutic framework revealed that many Korean clients reported that despite initial fears and needing to test their counselors, sharing their secrets was a powerful experience that deepened their connection to their counselor, facilitated positive life changes, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Disclosures mainly involved secrets that were the most difficult to reveal, including familial history, sexual identity, sexual experiences that have never been told to others and negative feelings toward counseling or the counselor. Clients reported that they recognized the necessity of disclosing these secrets and they believed their counselors were trustworthy but simultaneously also felt “extreme fear and shame” (Han and O’Brien, 2014). Inhibitions toward self-disclosure were reflected in the categories sharing difficult experience with one’s own family and musical experience as a way to explore emotions .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disclosures mainly involved secrets that were the most difficult to reveal, including familial history, sexual identity, sexual experiences that have never been told to others and negative feelings toward counseling or the counselor. Clients reported that they recognized the necessity of disclosing these secrets and they believed their counselors were trustworthy but simultaneously also felt “extreme fear and shame” (Han and O’Brien, 2014). Inhibitions toward self-disclosure were reflected in the categories sharing difficult experience with one’s own family and musical experience as a way to explore emotions .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, clinical suggestions have been formulated concerning the therapists’ attitude and way of interacting with the Korean clients have been discussed in a number of studies. Han and O’Brien (2014, p. 545) explained that therapists working with Korean clients need to exercise patience and seek to develop a strong therapeutic alliance prior to expecting “the real work of therapy to commence.” Joo (2009) stated several key elements are necessary to assist and enable clients to experience the therapeutic relationship as less hierarchal, including adopting an “inviting” attitude, developing “collaborative and egalitarian relationships,” and fostering “trust and honesty.” Moreover, therapists need to maintain consistency between their expression of emotion and action, avoid behaving authoritatively, and expressing their thoughts simultaneously (Joo and Park, 2016). Kim and Park (2016) indicated that therapists’ humor, honesty, self-disclosure, and empathy can be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found that most clients disclosed at least one secret to their therapist, typically about relationships and sex (Baumann & Hill, 2015). Clients, however, experienced ambivalence regarding the disclosure of secrets and other deeply personal material, feeling both the desire to disclose and the fear of doing so (Baumann & Hill, 2015; Farber, Berano, & Capobianco, 2004, 2006; Farber, Feldman, & Wright, 2014; Han & O’Brien, 2014). Factors that prompted a client to share a secret included trust in the therapist and a belief that the client could benefit from disclosing the secret (Baumann & Hill, 2015; Han & O’Brien, 2014).…”
Section: Disclosure Of Secrets In Psychotherapymentioning
confidence: 99%
“…Clients also experienced mixed emotions immediately after disclosing a secret, although they reported predominantly positive emotions about disclosing after the passage of time (Baumann & Hill, 2015; Farber et al, 2014). Furthermore, receiving a calm, nonjudgmental response from therapists helped clients to feel positive about their disclosure and to view the disclosure as the most important moment in therapy (Han & O’Brien, 2014).…”
Section: Disclosure Of Secrets In Psychotherapymentioning
confidence: 99%
See 1 more Smart Citation